Scanning Rate Enhancement of Leaky-Wave Antennas Using Slow-Wave Substrate Integrated Waveguide Structure - Guan, Dong-Fang; Zhang, Qingfeng; You, Peng; Yang, Zhang-Biao; Zhou, Yang; Yong, Shao-Wei (IEEE transactions on antennas and propagation, 2018)
In this communication, we propose a high scanning rate leaky-wave antenna (LWA) based on a slow-wave substrate integrated waveguide (SIW) structure. The slow-wave effect is introduced by etching periodical slots on the top surface of SIW. The LWA radiation is subsequently realized by introducing sinusoidal modulation to the slots profile. Such a structure significantly improves the scanning rate of LWA due to the small group velocity at the slow-wave region. Simulation and measured results indicate that the proposed LWA scans a wide angle in a narrow bandwidth near the cutoff frequency of surface plasmon polariton. Within the frequency band 13.5-13.9 GHz (3% relative bandwidth), the measured scanning angle is from 2° to 37° with the measured gain all above 9.2 dBi.